Pixel Overlapping Image Steganography Using PVD and Modulus Function - Sahu, Aditya Kumar; Swain, Gandharba (3D research, 2018)
This paper proposes an image steganography technique based on the principle of pixel overlapping to improve the embedding capacity (EC) and peak signal-to-noise ratio (PSNR). The proposed technique has two variants: (1) overlapped pixel value differencing with modulus function (OPVDMF), and (2) overlapped pixel value differencing (OPVD). Both the variants operate on pixel blocks of size 1 × 5. The OPVDMF uses the difference between the first four pixels with the 5th pixel for data embedding. Again the pixel adjustment is done to minimize the distortion. The OPVD method divides the block into four sub-blocks with 1st and 5th, 5th and 2nd, 3rd and 5th, 5th and 4th pixels. The proposed technique has been compared with the existing techniques in terms of PSNR, EC, bits per pixel, and execution time. Further, the security of the proposed technique has been verified using RS analysis. Graphical Abstract